2012
DOI: 10.1200/jco.2012.43.6055
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between End-of-Life Discussion Characteristics and Care Received Near Death: A Prospective Cohort Study

Abstract: A B S T R A C T PurposeNational guidelines recommend that discussions about end-of-life (EOL) care planning happen early for patients with incurable cancer. We do not know whether earlier EOL discussions lead to less aggressive care near death. We sought to evaluate the extent to which EOL discussion characteristics, such as timing, involved providers, and location, are associated with the aggressiveness of care received near death. Patients and MethodsWe studied 1,231 patients with stage IV lung or colorectal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
351
2
12

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 477 publications
(379 citation statements)
references
References 31 publications
14
351
2
12
Order By: Relevance
“…In the "Coping with Cancer" study, Wright et al showed that end-of-life discussion was signiicantly associated with a less aggressive medical care (such as ventilation, ICU admission, and resuscitation), a reduction in the bereaved caregiver's grief or depression, and a longer hospice stay [92]. Other similar studies also showed consistent results [1,93,94].…”
Section: Clinical Utility Of Prognostic Disclosuresupporting
confidence: 58%
“…In the "Coping with Cancer" study, Wright et al showed that end-of-life discussion was signiicantly associated with a less aggressive medical care (such as ventilation, ICU admission, and resuscitation), a reduction in the bereaved caregiver's grief or depression, and a longer hospice stay [92]. Other similar studies also showed consistent results [1,93,94].…”
Section: Clinical Utility Of Prognostic Disclosuresupporting
confidence: 58%
“…Being hesitant to stop futile palliative chemotherapy may lead to aggressive EOL care and life-sustaining treatment. Although discussion of EOL care has been shown to be associated with less aggressive EOL care [40], we still face difficult decisions about chemotherapy near the EOL among patients [13] and physicians. Physicians consistently overestimated prognosis by at least 30% [41]; their estimate of survival could be divided by 3.5 for actual survival [42].…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…Although most patients were able to talk about their wishes for end-of-life care before death, the timing mattered; patients who had earlier discussions were less likely to receive aggressive measures at the end of life and more likely to receive hospice care. 44 Thus, physicians of patients facing death may do well to start discussing this possibility early rather than at a later moment of crisis.…”
Section: Addressing and Managing Prognostic Uncertaintymentioning
confidence: 99%